A review in particle image velocimetry techniques (developments and applications) - Abdulwahab M.R.; Ali Y.H.; Habeeb F.J.; Borhana A.A.; Abdelrhman A.M.; Ali Al-Obaidi S.M. (Penerbit Akademia Baru, 2023)
The latest entrant into the fluid flow measurement field is the particle image velocimetry (PIV) which offers velocity field immediately in flow domains. Referring to the definition, the placement is recorded by PIV over time pertaining to small tracer particles that were released in the flow for local fluid velocity extraction. Thus, PIV can be regarded as a quantitative extension pertaining to visualisation techniques for qualitative flow being practiced for a number of decades. This review provides a detailed background pertaining to evolution of PIV, principle of operation, basic elements, key features, uncertainty, errors in PIV as well as few applications of PIV. Recent advances pertaining to the PIV technique have been aimed at procuring all three components with regards to fluid velocity vectors simultaneously in a volume or in a plane that enables wider applications with the PIV technique for investigating more complex flow phenomena. In recent years, developing of various advanced PIV techniques have been successfully achieved, including three-dimensional (3D) particle-tracking velocimetry (3D-PTV), tomographic PIV, holographic PIV (HPIV) technique and stereo PIV (SPIV). A comparison has been done between the main PIV techniques. 2020 Penerbit Akademia Baru.